2003
DOI: 10.1039/b210713a
|View full text |Cite
|
Sign up to set email alerts
|

Size- and shape-tailored hydrothermal synthesis of YVO4 crystals in ultra-wide pH range conditions

Abstract: Yttrium orthovanadate (YVO 4 ) crystals have been prepared hydrothermally in both strongly acidic and basic media. The effects of vanadium source, acid, addition of sodium hydroxide, chelating reagent, and even solvent on the crystalline size and shape were explored using X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Models for the generation of YVO 4 crystals in both acidic and basic media are proposed from the experimental results. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
66
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 56 publications
0
66
0
Order By: Relevance
“…According to SEM observations, the powder consisted of aggregated flakes, which included B10 nm spherical particles. A very similar morphology was described by H. Wu,11 when acetic acid was used as an additive in the hydrothermal synthesis of YVO 4 . The change from flake-like to raspberry-like shape became pronounced when the solution temperature exceeded the critical temperature of methanol.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…According to SEM observations, the powder consisted of aggregated flakes, which included B10 nm spherical particles. A very similar morphology was described by H. Wu,11 when acetic acid was used as an additive in the hydrothermal synthesis of YVO 4 . The change from flake-like to raspberry-like shape became pronounced when the solution temperature exceeded the critical temperature of methanol.…”
mentioning
confidence: 65%
“…Hydrothermal systems offer higher diffusivity and lower viscosity, which facilitates mass transport, while the solvents possess higher dissolving power. 10 Recently, the hydrothermal method was applied to the synthesis of YVO 4 by H. Wu et al, 11 who synthesized welldefined YVO 4 microcrystals with clear facets in strongly acidic media as well as nanoflakes with dimensions of 5-50 nm in basic media. X. Wu et al 12 reported the synthesis of YVO 4 nanorods and microtubes by the hydrothermal method using (NH 4 ) 0.5 V 2 O 5 nanowires and porous silicon as templates.…”
mentioning
confidence: 99%
“…The size of sample synthesized at neutral medium (pH ¼ 7) is much smaller than those at acidic and basic media. The dependence of particle size on pH value has been investigated in hydrothermal synthesis of YVO 4 [12,13]. In the basic media, the following reactions would occur:…”
mentioning
confidence: 99%
“…They have studied the influence of various experimental conditions including type of mineralizer, solution pH and process temperature on the growth of YVO4:Nd single crystals for possible laser applications. H. Wu et al 18) demonstrated that hydrothermal method can be used for the synthesis of YVO4 microcrystals as well, and strongly acidic solution favors formation of crystals with well-defined facets, while basic media results in precipitation of flakes of 5-50 nm size. (NH4)0.5V2O5 nanowires and porous silicon as templates allowed X. Wu et al 19) to prepare YVO4 in the form of nanorods and microtubes by the hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%